Analisis Hambatan dan Tantangan Implementasi Kartu Jakarta Mahasiswa Unggul di Lingkungan Universitas Negeri Padang - Rizkianur, Adlina; Magriasti, Lince (PUBLICNESS: Journal of Public Administration Studies, 2024)
This research aims to determine and analyze the obstacles and factors that become challenges in the implementation of the Jakarta Excellent Student Card (KJMU) Policy at Universitas Negeri Padang. This type of research is qualitative research using descriptive methods, data collection techniques in this research use interviews and documentation studies. The results of this research are the obstacles to the Jakarta Superior Student Card (KJMU) policy at Universitas Negeri Padang, namely the administration of KJMU which is not yet good, the absence of a decree from KJMU which is given to students and to BAK UNP, the difficulty of BAK UNP in determining KJMU recipients. new, and at the time of UKT payment, KJMU had not paid for the semester so the status was in arrears. The factors that become challenges in implementing the Jakarta Superior Student Card (KJMU) policy at Universitas Negri Padang are that KJMU Scholarship recipients are required to be able to maintain a GPA above 3, KJMU scholarship recipients are required to be active in organizations, and KJMU scholarship recipients are required to have entrepreneurial skills.